SUBSURFACE STRUCTURE OF BATURAGUNG ESCARPMENT REVEALED THROUGH THREE-DIMENSIONAL GRAVITY INVERSION - Selvi Misnia Irawati; Alutsyah Luthfian; Agus Laesanpura (Engineering Faculty Universitas Lampung, 2021)
Baturagung Escarpment is an essential tectonic element of Java Island because it represents a transition from the Southern Mountain Block to the Kendeng Basin. This study has succeeded in producing a three-dimensional model of the Baturagung Escarpment subsurface using gravity anomaly data. The data are distributed along a regional scale transect, whose resolving capability has been tested using a checkerboard test. Our proposed geophysical model can fit the observed data very well, with a 0.77% RMS error. This model exhibits a structural depression bounded by high basement blocks below the Baturagung Escarpment, one of the basement block outcrops at Jiwo Hills. The maximum width of the depression is 10 km, with a depth exceeding 3 km in some places. The depression might be formed because of an extensional tectonic regime that prevailed during the Palaeogene, followed by volcanic arc loads' emplacement up to the early Miocene.